2005
DOI: 10.1111/j.0022-1112.2005.00649.x
|View full text |Cite
|
Sign up to set email alerts
|

Individual feeding success of juvenile perch is consistent over time in aquaria and under farming conditions

Abstract: Juvenile (0+ year) perch Perca fluviatilis, held in tanks (1 m3) for 8 months under constant temperature (17° C) and light (12L : 12D) conditions, were weighed monthly. Individually marked fish from the tanks were placed in aquaria in groups of four and tested for feeding success, assessed as individual share of a group meal in three identical short‐term aquarium experiments separated in time (January, May and June). The groups consisted of the same individuals in each of the three experiments. In tanks, growt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
1
6
0
Order By: Relevance
“…As both experiments were performed during late spring and early summer, the increase in feed intake and growth with time may be the result of a release of a winter suppression of appetite and growth. Similar seasonal increases in feed intake and growth at constant temperatures have previously been noted for perch [39,40]. Nevertheless, the main results regarding the effect of temperature and body size on the growth, feed intake, and energy requirements of juvenile perch are not affected by the differences between the rounds.…”
Section: Body Size Datasupporting
confidence: 79%
See 1 more Smart Citation
“…As both experiments were performed during late spring and early summer, the increase in feed intake and growth with time may be the result of a release of a winter suppression of appetite and growth. Similar seasonal increases in feed intake and growth at constant temperatures have previously been noted for perch [39,40]. Nevertheless, the main results regarding the effect of temperature and body size on the growth, feed intake, and energy requirements of juvenile perch are not affected by the differences between the rounds.…”
Section: Body Size Datasupporting
confidence: 79%
“…By having different duration of the experimental rounds for high and low temperatures, respectively, identical numbers of replicates could be obtained for all temperatures while limiting the experiment to approximately two months. This was desirable in order to reduce season related variations in growth [39,40]. Groups of eight fish were used and initial average live weight (± SD) of the fish was 28.3 g (± 6.9).…”
Section: Methodsmentioning
confidence: 99%
“…2004). Obtaining a size advantage may occur through a number of routes, and competition (Staffan et al. 2005), density‐dependent growth (Byström & Garcia‐Berthou 1999) or ontogenetic diet shifts (Persson & Greenberg 1990; Olson 1996) influence growth rates of individual fish, leading to the occurrence of size divergence within age cohorts.…”
Section: Introductionmentioning
confidence: 99%
“…Individual growth is an important factor in the early life of fish determining their actual body size and therewith the potential to use certain food resources, the vulnerability to predators and the storage of energy in lipid reserves (Persson et al 2004). Obtaining a size advantage may occur through a number of routes, and competition (Staffan et al 2005), density-dependent growth (Byström & Garcia-Berthou 1999) or ontogenetic diet shifts (Persson & Greenberg 1990;Olson 1996) influence growth rates of individual fish, leading to the occurrence of size divergence within age cohorts. In many freshwater fishes, variation in body sizes within the young-of-the-year (YOY) cohort is typically driven by ontogenetic diet shifts (Persson & Brönmark 2002;Galarowicz & Wahl 2005).…”
Section: Introductionmentioning
confidence: 99%
“…In a number of examples, boldness levels are also positively associated with aggression (Huntingford, 1976; Bell & Stamps, 2004; Sundström et al , 2004; Bell, 2005; Bell & Sih, 2007). Other work has shown that boldness levels are also linked with fitness‐related traits (Smith & Blumstein, 2008), such as body size (Brown & Braithwaite, 2004; Brown et al , 2005), condition (Brown & Shine, 2007) and feeding performance (Staffan et al , 2005). These relationships suggest important ecological and evolutionary implications of behavioural syndromes, such as constraints on behavioural plasticity required for achieving optimal behaviour in all life contexts (Dall et al , 2004; Sih et al , 2004 b ; Smith & Blumstein, 2008).…”
Section: Introductionmentioning
confidence: 99%